Postgraduate students' attitudes towards the quality of e-learning: Students of the Great College of Imam Al-Adham (may Allah bless him) University – As a model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to know the attitudes of graduate students towards the qualityof e-learning from the point of view of the students of the College of Imam Al-Adham (mayAllah bless him) University. For the purpose of achieving the research goal, the researcherschose graduate students at the College of Imam Al-Adham (may Allah bless him) University, forthe departments (Quranic readings, Islamic studies in English, Arabic language, advocacy andpublic speaking, Fiqh and its Foundations, Religion basics), which numbered (145) male andfemale students, as the researchers adopted the descriptive approach and considered thequestionnaire a measuring tool consisting of two parts. The first part includes the generalinformation of the study members represented in their personal and occupational variables suchas (gender, academic qualification, and academicspecialty). As for the second part of thequestionnaire, it included fifteen questions about e-learning and about the nature of students’interaction with it in light of the nature of the research and the goals it seeks to achieve.Eachparagraph was met with an answer that follows a five-point scale (R language scale): Stronglyagree - Agree - Undecided - Disagree - Strongly disagree. Each response was given certaindegrees to be processed statistically and distributed to a group of experts and judges specializedin educational and psychological studies and teaching methods to ensure the apparent honesty.The researchers also adopted the (R language) program to process the data statistically to extractthe arithmetic mean, standard deviation and variance for all paragraphs.